Utility of presepsin (sCD14-ST) as a diagnostic and prognostic marker of sepsis in the emergency department - Carpio, Ricardo (2015)
Presepsin (PSEP) is released during infectious diseases and can be detected in the blood. PSEP has shown promising results as sepsis marker. We examined the diagnostic and prognostic validity of PSEP in patients suspicious of sepsis on admission in the emergency department (ED). Methods One hundred twenty three patients with signs of SIRS and/or sepsis and 123 healthy individuals were enrolled. PSEP was determined on admission, after 8, 24 and 72 h. Results Mean PSEP concentrations of the control group and the patient group were 130 and 1945 pg/ml. PSEP differed between SIRS, sepsis, severe sepsis and septic shock and showed strong association with 30-day mortality ranging from 10.3% in the 1st to 32.1% in the 4th quartile. The ROC curve analyses revealed an AUC value of 0.743. Combined assessment of PSEP and MEDS score increased the AUC up to 0.878 demonstrating the close relationship with outcome. Based on the PSEP values in the different severity degrees, decision thresholds for risk stratification were established. The course of PSEP during the first 72 h was associated with effectiveness of treatment and outcome. Conclusions PSEP allowed outcome prediction already on admission to a similar degree as the clinical scores MEDS and APACHE II. Combination of PSEP with MEDS score improved the discriminatory power for outcome prediction.